A Reflection Of Societal Norms In Mahesh Dattani’s ‘Tara’ - et. al., Vinita Marigold , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Literature is said to hold a mirror up to society. The public and the personal aspects of one’s life is woven with words into fabric that is exhibited to others in various forms –it could be prose, poetry, drama or novel. From the pre-Independence era, drama served as a platform to show case the social structural patterns, the beliefs, the injustices, concerns of a particular society in a particular time or era. Modern Indian drama plays two keys roles today. Firstly, it is closely related to modern Indian life-with people and society and secondly it keeps different regions, classes and castes united yet related. With the theory of socialistic feminism, an attempt has been made to showcase the injustices of the time in the name of customs or practices or social norms in Mahesh Dattani’s Tara. The Siamese conjoined twins Chandan and Tara have a battle against society. Their desire is a life of normalcy and in the process a need for acceptance. But the attempt to acquire normalcy does not seem small and the efforts are many and far reaching and above all partial and sinister.